2021
DOI: 10.1002/ptr.7046
|View full text |Cite
|
Sign up to set email alerts
|

Promising influences ofScutellaria baicalensisand its two active constituents, baicalin, and baicalein, against metabolic syndrome: A review

Abstract: Metabolic syndrome is known as a group of metabolic abnormalities with features including central obesity, insulin resistance, hypercholesterolemia, hypertriglyceridemia, and hypertension as well as low level of high-density lipoprotein (HDL)-cholesterol. Previous studies showed the ameliorating effects of Scutellaria baicalensis on metabolic syndrome parameters, including antidiabetic, anti-hyperlipidemic, anti-obesity, and antihypertensive. In this review, we deeply and mechanistically evaluated different st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 125 publications
(156 reference statements)
0
30
0
Order By: Relevance
“…Chronic inflammation occurs when the inflammation goes out of physiological condition. These conditions are seen in some diseases such as metabolic syndrome, rheumatoid arthritis, psoriasis, osteoarthritis, and cancer [ 16 20 ]. Eventually, chronic inflammation causes inflammatory disorders and pain through the secretion of inflammatory mediators, including prostaglandins, nitric oxide (NO), interferon γ (IFN- γ ), and histamine [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chronic inflammation occurs when the inflammation goes out of physiological condition. These conditions are seen in some diseases such as metabolic syndrome, rheumatoid arthritis, psoriasis, osteoarthritis, and cancer [ 16 20 ]. Eventually, chronic inflammation causes inflammatory disorders and pain through the secretion of inflammatory mediators, including prostaglandins, nitric oxide (NO), interferon γ (IFN- γ ), and histamine [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…S. baicalensis is widely used in traditional medicine, and its main bioactive flavonoids, baicalin and baicalein, have been found to have diverse beneficial activities, including antioxidant and anti-inflammatory effects [ 37 , 38 ]. They are being extensively studied for the treatment of various metabolic syndromes, respiratory diseases, autoimmune diseases, cancers, and inflammatory diseases in different organs [ 37 , 38 ]. Root extracts of S. baicalensis and its major components, baicalin and baicalein, have also been reported to exhibit anti-inflammatory effects on AD-induced NC/Nga mice [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…S. baicalensis is widely used in traditional medicine, and its main bioactive flavonoids, baicalin and baicalein, have been found to have diverse beneficial activities, including antioxidant and anti-inflammatory effects [37,38]. They are being extensively studied for the .…”
Section: Discussionmentioning
confidence: 99%
“…Several attempts have been made to prove that BG notably inhibited the activities of OATs and significantly decrease the influx of OATs substrates ( Xu et al, 2013 ). A number of researchers have sought to determine that oral administration of BG rapidly converted to baicalin (B) on the intestinal microflora and B dominantly metabolized to BG in the liver ( Baradaran Rahimi et al, 2021 ; Hu et al, 2021 ). Peng Xu et al reported B could alter the pharmacokinetic and pharmacodynamic profiles of silybin significantly by inhibition of BCRP and MRP2 ( Xu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%